2021
DOI: 10.1039/d0ee03295f
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study of electrode materials for rechargeable batteries beyond lithium ions byin situtransmission electron microscopy

Abstract: Understanding the fundamental mechanisms of advanced electrode materials at the atomic scale during the electrochemical process is condemnatory to develop the high-performance rechargeable batteries. The complex electrochemical reactions involved inside...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 198 publications
0
33
0
Order By: Relevance
“…This may be a possible and promising solution to obtain high-voltage and long-durability LICs. Furthermore, some in situ and ex situ characterization technologies could be applied to investigate the decomposition mechanism of electrolytes, the degradation and/or evolution of the electrode surface and electrode/electrolyte interface and the composition of decomposed products [ 145 , 146 , 147 ]. It is expected that these in situ and ex situ tools will help us to understand the beneath decomposition mechanism and find an effective protection method.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a possible and promising solution to obtain high-voltage and long-durability LICs. Furthermore, some in situ and ex situ characterization technologies could be applied to investigate the decomposition mechanism of electrolytes, the degradation and/or evolution of the electrode surface and electrode/electrolyte interface and the composition of decomposed products [ 145 , 146 , 147 ]. It is expected that these in situ and ex situ tools will help us to understand the beneath decomposition mechanism and find an effective protection method.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] While a large amount of research activity has focused on lithium and sodium-ion batteries, there are not too many literatures in the field of PIBs. [20][21][22] Although Te is tested as a cathode for PIBs, the proposed reaction mechanisms remain controversial. Shuai et al reported a Te/porous carbon composite for KIB, delivering a high capacity and rate performance.…”
Section: Research Articlementioning
confidence: 99%
“…[27][28][29] It has the unique merit of providing direct insights into dynamic compositional and microstructural evolutions during electrochemical reactions in electrodes. [21,30] Here, we explore the atomistic (de)potassiation mechanism of single crystalline Te nanowires (NWs) using both in situ X-ray diffraction and in situ TEM including high-resolution transmission electron microscopy (HRTEM) imaging and dynamic electron diffraction (ED). [31] We discover a two-step potassiation mechanism involving a Te-to-K 2 Te 3 transition in the first stage and an incompletely K 2 Te 3 -to-K 5 Te 3 transition in the second stage.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Besides monovalent cation batteries (LIBs/SIBs/PIBs), rechargeable ion batteries based on multivalent cations such as Mg 2+ , Al 3+ , Zn 2+ can be the future energy storage devices due to their high energy density, low cost, and relatively large abundance in the Earth's crust [260][261][262][263]. The working principle of multi-IBs is similar to that of mono-valent ion batteries (LIBs/ SIBs/PIBs) in many ways, except the use of multivalent ion instead of mono-valent ion.…”
Section: Mibsmentioning
confidence: 99%